Caryota urens and Hyophorbe lagenicaulis as Nutraceutical by Managing Commercially Available Drug Induced Nephrotoxicity - Das, Saumya; Shakya, Richa; Mazumder, Avijit; Gautam, Anamaika (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Caryota urens flowers and Hyophorbe lagenicaulis leaves have huge beneficial properties, medicinal uses and rich phyto-pharmacological constituents. Nutraceutical potentiality of the selected plants on the basis of phytochemicals present in the aerial parts of Caryota urens and Hyophorbe lagenicaulis were taken as the background of the study. Aim: The present study investigates the nephroprotective potentiality of Caryota urens flowers and Hyophorbe lagenicaulis leaves against cisplatin and gentamycin induced nephrotoxicity. Materials and Methods: The extract of Caryota urens flowers and Hyophorbe lagenicaulis leaves were screened for preliminary phytochemical analysis. The in vitro antioxidant activity of Caryota urens flower extract (CUFE) and Hyophorbe lagenicaulis leaves extract (HLLE) was performed by DPPH and H₂O₂ radical scavenging activity. In vivo acute oral toxicity test was performed by following OECD guideline 420. The screening models for cisplatin and gentamycin induced nephrotoxicity by using albino Wistar rats were also carried out. Results: In in vitro antioxidant studies CUFE and HLLE (*p<0.01 and **p<0.001) for both standard and test drugs. It also act as potent nutraceuticals in cisplatin and gentamycin induced nephrotoxicity (**p<0.001). No major side effects were seen in any of the experimental animal during acute oral toxicity. Conclusion: CUFE and HLLE (1:1) have nutritionally rich source of dietary food supplements and due to this they are also helpful in managing the commercial drugs induced nephrotoxicity.
Keywords: Nutraceuticals; Phytochemical; Cisplatin; Gentamycin; Nephrotoxicity